Promoting Effects of Heparin on ex vivo Expansion of Megakaryocytopoiesis from Human Cord Blood CD34+Cells - (:unkn) unknown (KARGER, 2013)
Introduction: Transfusion of ex vivo expanded megakaryocytes (MKs) has been proposed to sustain platelet recovery after cord blood (CB) hematopoietic stem cell transplantation. In this study, we investigated the effects of heparin on ex vivo colony forming unit-megakaryocytes (CFU-MKs) and MKs expansion from CB CD34+ cells. Methods: CB CD34+ cells were stimulated by a combination of thrombopoietin (TPO), stem cell factor (SCF), Flt3-Ligand (FL), IL-6, and IL-11 supplemented with autologous serum and heparin during 14 days. Expanded cells were analyzed by flow cytometry and cultured in a CFU-MK assay. Results: Compared to control cultures, the 5-factor combination with heparin induced significantly (p < 0.05) higher numbers of: CFU-MKs and CD41+ cells on days 7 and 14; CD41+ cells displaying hyperploidy levels (>= 8N) on day 14; platelets on day 14. The culture-derived platelets were activated upon collagen stimulation. Conclusion: Heparin can significantly enhance the stimulating effects of a combination of TPO, SCF, FL, IL-6, and IL-11 supplemented with autologous serum on CFU-MK, MK, and platelet production from CB CD34+ cells. This expansion system could represent a promising method to generate CFU-MKs and MKs cells for transfusion to sustain platelet reconstitution following CB transplantation.
Keywords: Megakaryocytopoiesis; Glycosaminoglycan; Expansion; Cord blood; CD34+cells; HEMATOPOIETIC PROGENITOR CELLS; EXTRACELLULAR-MATRIX; IN-VITRO; TRANSPLANTATION; THROMBOPOIETIN; SULFATE; GLYCOSAMINOGLYCANS; COMBINATION; CYTOKINES